Study of clinical outcome of single intra-articular injection of artificial hyaluronic acid preparation in patients with grade III and grade IV knee osteoarthritis - Choudhary, Sumedh; Ghoti, Santosh (International Journal of Research in Orthopaedics, 2022)
Background: Knee osteoarthritis (OA) is problematic in elderlies. Intra-articular injection of hyaluronic acid (HA) has been used with good results in patients with early OA, but evidence to recommend their use in late stages is insufficient. The aim of the study was to analyse whether intra-articular injections of hyaluronic acid preparation can provide relief in patients with grade III and grade IV knee OA. Methods: This observational study was conducted over 2 years amongst patients with late knee arthritis. On standing radiographs, patients were categorized- group 1 with stage III and group 2 with stage IV knee OA. Standardized technique was employed in all participants for single shot intra-articular hylan-GF-20 injection. Clinical outcomes were evaluated at 3, 6 and 12 months. Results: Group 1 patients showed significant improvement in Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores at 3, 6 and 12 months (p<0.05). In group 2, improvement was noted in WOMAC score for pain and function at 3 months (p<0.05). There was no significant improvement in functional and total WOMAC score at 6 and 12 months (p>0.05). Results for the new OA research society international (OARSI) responder criteria measures for proposition D reflected that, 94.87% and 25% patients were responder and 5.13% and 75% of patients were non-responder in group 1 (grade III) and group 2 (grade IV) respectively at the end of 6 months. Conclusions: In patients with grade III and grade IV knee OA, a single intra-articular injection of HA preparation (Hylan GF-20) showed pain relief for medium and short duration respectively. TKA remains the mainstay of management.